Proclus' On the Hieratic Art according to the Greeks : Critical Edition with Translation and Commentary - Pachoumi, Eleni (Classical Studies E-Books Online, Collection 2024., 2024)
The book is a critical edition of the text with an English translation and commentary of Proclus' On the Hieratic Art according to the Greeks . The Hieratic Art is the Theurgic Art, theurgy, the theurgic union with the divine. Proclus describes the theurgic union, putting an emphasis on a conceptual blending of ritual actions (teletai, e.g. the role of statues, incenses, synthêmata, symbols, purifications, invocations and epiphanies) and philosophical concepts (e.g. union of many powers, 'one and many', symphathy, natural sympathies, attraction, mixing and division).